2014
DOI: 10.5498/wjp.v4.i4.103
|View full text |Cite
|
Sign up to set email alerts
|

Peptides from adipose tissue in mental disorders

Abstract: Adipose tissue is a dynamic endocrine organ that is essential to regulation of metabolism in humans. A new approach to mental disorders led to research on involvement of adipokines in the etiology of mental disorders and mood states and their impact on the health status of psychiatric patients, as well as the effects of treatment for mental health disorders on plasma levels of adipokines. There is evidence that disturbances in adipokine secretion are important in the pathogenesis, clinical presentation and out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 112 publications
(123 reference statements)
2
19
1
Order By: Relevance
“…The authors suggested that the lack of leptin or resistance to its action could favor a depressive status, and this factor could lead to worsening of fibromyalgia. The leptin levels are decreased in depression, and the administration of leptin may improve depressive symptoms (31). In the present study, mood changes, as determined by the PHQ-9, showed no difference between the two fibromyalgia groups.…”
Section: Discussioncontrasting
confidence: 54%
“…The authors suggested that the lack of leptin or resistance to its action could favor a depressive status, and this factor could lead to worsening of fibromyalgia. The leptin levels are decreased in depression, and the administration of leptin may improve depressive symptoms (31). In the present study, mood changes, as determined by the PHQ-9, showed no difference between the two fibromyalgia groups.…”
Section: Discussioncontrasting
confidence: 54%
“…Obesity and diabetes are also associated with disruption of PFC circuits and neurotransmitter systems (i.e., serotonin, dopamine, endocannabinoids, opioids) involved in motivation, reward, and anxiety that overlap with depression circuits 80,8789 . Circulating peptides, including leptin and adiponectin (from adipose tissue) and ghrelin (from stomach), which influence feeding behavior and/or energy homeostasis 90 , are also regulated by stress and influence depression and anxiety behavior in rodent models 9193,94 . Feeding, energy homeostasis, endocrine and neurocrine systems are also influenced by the gut microbiome, which has been implicated in healthy behavior while an imbalanced microbiome-brain interaction has been linked with psychiatric illnesses, including depression and anxiety 9597 .…”
Section: Metabolic Imbalance and Diabetes: Peptides And Related Signamentioning
confidence: 99%
“…Modifications of leptin metabolism and its gene expression, as well as its receptor, have been reported among patients with mental health disorders, independently to psychotropic drugs or in absence of antipsychotics [43]. Several studies showed a particular interest in the relationship between leptin and depressive disorders, but with discordant conclusions [42][43][44][45].…”
Section: Leptin and Psychiatric Illnessesmentioning
confidence: 99%